Best Paper Award - Loizou, Christos P. (My University, 2026)
Best Student Paper: A. Nicolaou, C. P. Loizou, M. Pantzaris, A. Kakas, C. S. Pattichis, “Rule extraction in the assessment of brain MRI lesions in multiple sclerosis: Preliminary findings”, 19th Int. Conf. Comp. Anal. Imag. & Patterns, N. Tsapatsoulis et al. (Eds.), CAIP 2021, Virtual Conference, LNCS 13052, Proc. Part I, pp. 277-286, Sept. 28-30, Nicosia, Cyprus, 2021.
Keywords: Sciences